Highly Enantioselective Adsorption of Small Prochiral Molecules on a Chiral Intermetallic Compound1. (29th January 2015) - Prinz, Jan; Gröning, Oliver; Brune, Harald; Widmer, Roland
Abstract Intrinsically chiral surfaces of intermetallic compounds are shown to be novel materials for enantioselective processes. Their advantage is the significantly higher thermal and chemical stability, and therefore their extended application range for catalyzed chiral reactions compared to surfaces templated with chiral molecular modifiers or auxiliaries. On the Pd1‐terminated PdGa(111) surface, room‐temperature adsorption of a small prochiral molecule (9‐ethynylphenanthrene) leads to exceptionally high enantiomeric excess ratios of up to 98 %. Our findings highlight the great potential of intrinsically chiral intermetallic compounds for the development of novel, enantioselective catalysts that can be operated at high temperatures and potentially also in harsh chemical environments.